Investigating Parallel Programming Paradigms in HeMPS MPSoC Platform - Lopes, Geaninne; Mello, Aline; Carvalho, Ewerson; Marcon, César (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2019: Anais do XX Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2019.8665, 2019)
This work investigates the use of parallel programming paradigms in the development of applications targeting a Multiprocessor System-on-Chip (MPSoC). We implemented Matrix Multiplication, Image Manipulation and Advanced Encryption Standard (AES) applications in the Master-Slave, Pipeline and Divide-and-Conquer paradigms, and applied execution time and power dissipation as criteria for evaluating the performance of the applications executing according to the paradigms on an MPSoC architecture. The obtained results allowed ​us to conclude that there are optimal application-paradigm relations. Pipeline presents lower execution time and lower power dissipation for the Image Manipulation application; whereas, Master-Slave performs better for the Matrix Multiplication and AES applications. However, when the input size of the applications increases, the Divide-and-Conquer paradigm tends to minimize the execution time for Matrix Multiplication application. ​The main contributions of this work are the development of applications, considering different paradigms, and the impact evaluation of these paradigms on MPSoC architecture.